2021
DOI: 10.1016/j.ejphar.2021.174248
|View full text |Cite
|
Sign up to set email alerts
|

Interferon therapy in patients with SARS, MERS, and COVID-19: A systematic review and meta-analysis of clinical studies

Abstract: Concern regarding coronavirus (CoV) outbreaks has stayed relevant to global health in the last decades. Emerging COVID-19 infection, caused by the novel SARS-CoV2, is now a pandemic, bringing a substantial burden to human health. Interferon (IFN), combined with other antivirals and various treatments, has been used to treat and prevent MERS-CoV, SARS-CoV, and SARS-CoV2 infections. We aimed to assess the clinical efficacy of IFN-based treatments and combinational therapy with antivirals, corticosteroids, tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 150 publications
(659 reference statements)
3
23
0
Order By: Relevance
“…Specifically, infection with the SARS virus can lead to a weakness of the immune tolerance to some antigens in lung tissue and the production of autoantibodies, resulting in severe lung tissue damage (14). Additionally, there is evidence hormonotherapy applied in SARS treatment not only contributes to the enhancement of autoimmune tolerance of patients, but also leads to a shorter duration of hospital stay (15). In the present study, a similar effect was found in that the length of stay in hospital of patients with COVID-19 who underwent hormonotherapy was reduced.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, infection with the SARS virus can lead to a weakness of the immune tolerance to some antigens in lung tissue and the production of autoantibodies, resulting in severe lung tissue damage (14). Additionally, there is evidence hormonotherapy applied in SARS treatment not only contributes to the enhancement of autoimmune tolerance of patients, but also leads to a shorter duration of hospital stay (15). In the present study, a similar effect was found in that the length of stay in hospital of patients with COVID-19 who underwent hormonotherapy was reduced.…”
Section: Discussionsupporting
confidence: 82%
“…Among various human CoVs, SARS‐CoV‐2 caused a severe mortality rate close to 1.38, and the most common symptoms in positive cases were cough, fever, headache, fatigue, diarrhea, and blood‐stained mucous. In the current scenario, the characterization of novel biomarkers which may play an important role in prediction and observation in the status of SARS‐CoV‐2 disease is required 13,14 . (p. 2)…”
Section: Introductionmentioning
confidence: 99%
“…In the current scenario, the characterization of novel biomarkers which may play an important role in prediction and observation in the status of SARS‐CoV‐2 disease is required. 13 , 14 (p. 2)…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, inborn defects in the IFN system or auto-antibodies against type I IFNs are frequently associated with severe disease [10,11]. Thus, IFN is currently evaluated in clinical trials as a therapeutic approach [20].…”
Section: Introductionmentioning
confidence: 99%